The role of Helicobacter in gastric cancer prevention - Mohammed Al Ghamdi, Khalid; Bawareth, Rozana Louai; Kankouni, Mohammad Waleed; Alaidarous, Hussain Ali; Almutairi, Saud Mansour; Almalki, Wajih Mohammed; Alotaibi, Kawakib Mohammed; Zouman, Ali M.; Al Rahma, Husain Ali; Almulla, Ahmad A.; Alghamdi, Mohammed Abdullah (International Journal Of Community Medicine And Public Health, 2025)
Gastric cancer is one of the most common cancers worldwide. It is associated with high mortality risk. Helicobacter pylori (H. pylori) is a major significant risk factor for gastric cancer, as its virulence factors significantly contribute to gastric carcinogenesis. H. pylori eradication has been associated with reduced incidence of gastric cancer. H. pylori mechanisms in achieving long-term and sustained cancer prevention remain unclear. The aim of this review is to explore the effectiveness and mechanisms of H. pylori in gastric cancer prevention. H. pylori contribute to gastric cancer by molecular mechanisms, such as activating the NF-κB pathway, and cellular mechanisms, such as oxidative stress. Studies have shown that H. pylori eradication reduced the incidence of gastric cancer in healthy populations and patients with early gastric cancer undergoing endoscopic mucosal resection. H. pylori vaccination can be an effective method in the prevention of H. pylori infection, thus preventing gastric cancer. Future studies should develop an integrated approach combining targeted eradication, microbiome management, and innovative vaccination strategies to prevent the occurrence of gastric cancer.